Determinan Tingkat Partisipasi Angkatan Kerja (Tpak) dan Inflasi Terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Santoso, Agus; Laseta, Apriyossy; Hierdawati, Trie; Siswoyo Siswoyo; Dani, Rian (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of TPAK and inflation on economic growth in Jambi Province in 2013 - 2022. The object of this research is TPAK and inflation as well as economic growth in Jambi Province. The analytical method used in the research is descriptive quantitative and the analytical tools used in this research are hypothesis testing (f test, t test), multiple linear analysis, R square coefficient of determination test, all data is processed using SPSS. The results of this research reveal the R-square value or coefficient of determination 0.247, which means that the influence of TPAK and inflation in Jambi Province can have an ability of 24.7% in explaining economic growth in Jambi Province, while (100% - 24.7% = 75.3%) is influenced by other factors outside the research variables. The significant test carried out on the TPAK (X1) table is seen from the t-count and t-table values. From the results of the regression carried out, it was obtained that the t-count value was -0.205 and the t-table value was 2.365, so the t-count value < t-table ( -0.205 < 2.365) with a probability sig value of 0.843 > 0.05. So Ho is accepted and Ha is rejected. This means that TPAK has no influence and is not significant on economic growth in Jambi Province. The significant test carried out on the Inflation variable (X2) can be seen from the t-count and t-table values. From the results of the regression carried out, it was obtained that the t-count value was 927 and the t-table value was 2.365, so the t-count value < t-table (927 < 2.365) with a probability value of Sig 0.385 > 0.05. So Ho is accepted and Ha is rejected. This means that inflation has no influence and is not significant on economic growth (Y) in Jambi Province.